Liquidity and Capital of Islamic Banks in Indonesia - Muhammad Nadratuzzaman Hosen; Syafaat Muhari (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
This study is aimed to analyzed the factors that affect the liquidity and capital of Islamic banks in Indonesia. The method is used multiple linear regression. This result shows that the main problem of Islamic banks in Indonesia is how to increase equity in line with increasing third party fund. Another problem is that Islamic bank face difficulties to find debt for solving liquidity problem due to lack of instruments for liquidity derivative. Therefore Islamic banks rely on third party funds, which are high cost of funds due to time deposit fund, rather than using current deposit and saving deposit fund. Another result, negative coefficient of Gross Domestic Product (GDP) to Quick Ratio (QR) indicate that if macroeconomics of Indonesia is stable and good environment, Islamic banks will expansive the market, meanwhile Islamic banks have now low level of liquidity buffer. This means Islamic banks face high level of risk, if core depositors withdraw money rushly it became defaultDOI: 10.15408/sjie.v6i1.4405